Kekuatan Keterangan Saksi Verbalisan Ditinjau Dari Segi Pembuktian - Alfian Alfandi; Fadli A. Natsif (Law Department, Universitas Islam Negeri Alauddin Makassar, 2022)
This study aims to determine how the position of verbalized witnesses in the Criminal Procedure Code, and also to find out what factors caused verbalized witnesses to be presented in the trial process and to find out how the strength of evidence against verbalized witness statements was carried out in the Makassar District Court, using research methods qualitative field method by going directly to the field by conducting interviews with judges, besides that the author also takes a theoretical basis by studying books, scientific works, articles and laws and regulations relating to the title of the thesis and the problem of the object of research. The results of the research obtained are: 1) The position of verbal witnesses is not regulated in the Criminal Procedure Code but regarding the meaning of verbal witnesses, namely the judge takes the legal basis from the decision of the Constitutional Court Number 65/PUU-VIII/2010. As the legal basis for verbal witnesses. 2) Factors that cause verbal witnesses to be presented in the trial process because the defendant or witness denies his actions or does not admit the mistakes contained in the Investigation Report. (BAP).